Produksi Bioetanol Limbah Nasi Aking Fermentasi Menggunakan Zymomonas mobilis dengan Perlakuan Konsentrasi Crude Enzim Bacillus amyloliquefaciens - Sekar Widyastanti; Trianik Widyaningrum (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2022)
Bioethanol fuel has the advantage of being more environmentally friendly than petroleum. Bioethanol is made from organic materials containing glucose. Baking rice contains 83.19% (w/w) carbohydrates and 29.70% (w/w) amylose which can be converted into bioethanol through hydrolysis and fermentation stages. This type of research is an experimental research, the initial stage carried out is the hydrolysis stage to obtain reducing sugars using crude Bacillus amyloliquefaciens enzymes with concentrations of 0%, 2.5%, 5%, 7.5%, 10%, 12.5%, 15 %, and 17.5% for 6 days. The next step is the fermentation stage to convert reducing sugar into ethanol using Zymomonas mobilis at a concentration of 10% for 4 days. And the final result is the distillation stage and the calculation of bioethanol levels using an alcohol meter. During the hydrolysis and fermentation processes, the sugar content was measured using the DNS (Dinitrosalicylic acid) method and the highest average sugar content was obtained at 10% Bacillus amyloliquefaciens concentration, namely 1.417 g/mL. The highest bioethanol content obtained was 3.03% at 10% Bacillus amyloliquefaciens concentration and the lowest bioethanol content was 0.61% at 0% Bacillus amyloliquefaciens concentration.